1994
DOI: 10.1002/ijc.2910560623
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxicity and characterization of an active metabolite of benzamide riboside, a novel inhibitor of IMP dehydrogenase

Abstract: Benzamide riboside exhibits significant cytotoxicity against a variety of human tumor cells in culture. On the basis of metabolic studies, the primary target of this drug's action appears to be IMP dehydrogenase (IMPDH). Incubation of human myelogenous leukemia K562 cells with an IC50 concentration of benzamide riboside resulted in an expansion of IMP pools (5.9-fold), with a parallel reduction in the concentration of GMP (90%), GDP (63%), GTP (55%) and dGTP (40%). On kinetic grounds, it was deduced that benza… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
24
2

Year Published

1994
1994
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 18 publications
(8 reference statements)
2
24
2
Order By: Relevance
“…13,14,40 The oncolytic activity of BR 3 was assumed to be due to its IMPDH-inhibitory and, therefore, dGTP-limiting action. 2,12 This hypothesis was strongly encouraged by the observation, that guanosine, a precursor of dGTP, prevented the oncolytic activity of BR. 12,41 Our findings show, that 5 mM BR induced apoptosis, whereas 20 mM BR provoked necrosis, although both concentrations of BR inhibited dGTP synthesis to a similar degree.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…13,14,40 The oncolytic activity of BR 3 was assumed to be due to its IMPDH-inhibitory and, therefore, dGTP-limiting action. 2,12 This hypothesis was strongly encouraged by the observation, that guanosine, a precursor of dGTP, prevented the oncolytic activity of BR. 12,41 Our findings show, that 5 mM BR induced apoptosis, whereas 20 mM BR provoked necrosis, although both concentrations of BR inhibited dGTP synthesis to a similar degree.…”
Section: Discussionmentioning
confidence: 99%
“…9 ± 11 BR, exhibited stronger antiproliferative activity in the K562 cells than TR 12 and was shown to induce apoptosis in HL-60 13 and N.1 ovarian carcinoma cells. 13,14 Higher BR-concentrations however, provoked necrosis, which is a common phenomenon of pro-apoptotic drugs 15 ± 17 and limits chemotherapy because of non-specific drug toxicity.…”
Section: Introductionmentioning
confidence: 99%
“…7 TR is an inhibitor of IMPDH 8 and Phase I/II clinical trials conducted with this compound in acute myelogenous leukaemia patients, indicated a significant reduction in leukaemic cell burden. 9 ± 11 BR, exhibited stronger antiproliferative activity in the K562 cells than TR 12 and was shown to induce apoptosis in HL-60 13 and N.1 ovarian carcinoma cells. 13,14 Higher BR-concentrations however, provoked necrosis, which is a common phenomenon of pro-apoptotic drugs 15 ± 17 and limits chemotherapy because of non-specific drug toxicity.…”
Section: Introductionmentioning
confidence: 99%
“…17 ± 19 It was postulated that BR exerts its anti-tumour effects due to IMPDH inhibition. 2,12 Therefore dGTP and other dNTP levels were analyzed and correlated with cell death modes. The necrotic trigger of high BR-concentrations was identified as DNA-clastogenic activity, which subsequently led to ATP depletion.…”
Section: Introductionmentioning
confidence: 99%
“…10,11 BR exhibited stronger antiproliferative activity in the K562 cells than TR. 12 The two nucleoside antimetabolites, TR and BR are converted in cancer cells to their active dinucleotide metabolites, TAD (thiazole-4-carboxamide adenine dinucleotide) and BAD (benzamide adenine dinucleotide), which are analogues of NAD, wherein the nicotinamide moiety is replaced by their respective bases. 11,13 BAD potently inhibits NAD utilization by IMPDH, resulting in the depletion of intracellular guanylate concentrations including GTP and dGTP.…”
Section: Introductionmentioning
confidence: 99%